2018
DOI: 10.1021/acs.iecr.7b04166
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Four-Way Plasma-Catalytic Approach for The After-Treatment of Diesel Engine Exhausts

Abstract: This study proposes a novel four-way plasma-catalytic removal of particulate matter, nitrogen oxides, hydrocarbons, and carbon monoxide without external heating using a pulsed dielectric barrier discharge reactor combined with Au/CaSO4/γ-Al2O3 catalyst balls. With the optimized amount of Au and CaSO4, over 90% of particulate matter, 40% of nitrogen oxides, and nearly 100% of hydrocarbons were removed from the diesel engine exhaust, while the increase of carbon monoxide concentration due to the oxidation of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Yao et al found that an Au- and CaSO 4 -impregnated γ-Al 2 O 3 catalyst was more effective for plasma-assisted DPM removal than an Au-impregnated γ-Al 2 O 3 catalyst. This study also demonstrated that the removal of DPM from the exhaust of a diesel power generator using a DBD reactor with an Au- and CaSO 4 -impregnated γ-Al 2 O 3 catalyst was as high as 91% . In fact, this level is comparable to that of a DPF, indicating that plasma catalysis is practicable for DPM removal.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Yao et al found that an Au- and CaSO 4 -impregnated γ-Al 2 O 3 catalyst was more effective for plasma-assisted DPM removal than an Au-impregnated γ-Al 2 O 3 catalyst. This study also demonstrated that the removal of DPM from the exhaust of a diesel power generator using a DBD reactor with an Au- and CaSO 4 -impregnated γ-Al 2 O 3 catalyst was as high as 91% . In fact, this level is comparable to that of a DPF, indicating that plasma catalysis is practicable for DPM removal.…”
Section: Introductionmentioning
confidence: 58%
“…This study also demonstrated that the removal of DPM from the exhaust of a diesel power generator using a DBD reactor with an Au-and CaSO 4 -impregnated γ-Al 2 O 3 catalyst was as high as 91%. 27 In fact, this level is comparable to that of a DPF, indicating that plasma catalysis is practicable for DPM removal. Unfortunately, the mechanism by which sulfates promote DPM oxidation in a plasma-assisted context remains poorly understood.…”
Section: Introductionmentioning
confidence: 92%
“…20 A large number of studies reported that PM, CO, HC can be used as reductants for NO x removal, and NO x can accelerate PM, CO, HC oxidation by the method of NTP combined with catalysts. [21][22][23] In previous studies, we prepared woody perovskite-type catalysts by biotemplating method combined with sol-gel method, and tested their purification performance. The results revealed that woody La 0.8 Ce 0.2-Fe 0.3 Co 0.7 O 3 can simultaneously purify PM, NO x , HC and CO emitted by engines.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Pan et al showed that NTP can enhance the purification performance of catalyst through the strong interaction between plasma and catalyst 20 . A large number of studies reported that PM, CO, HC can be used as reductants for NO x removal, and NO x can accelerate PM, CO, HC oxidation by the method of NTP combined with catalysts 21–23 . In previous studies, we prepared woody perovskite‐type catalysts by bio‐templating method combined with sol–gel method, and tested their purification performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, NTP-catalysis technology has been successfully applied to reduce the production of PM in the field of volatile organic chemical decomposition [29][30][31][32][33][34][35][36][37], which has been anticipated to be one of the alternative techniques for UFP removal. Meanwhile, it has been found that particles in the range of 20-100 nm are rarely produced in the decomposition processes of benzene using a dielectric barrier discharge (DBD) reactor with CeO 2 /γ-Al 2 O 3 catalysts [38][39][40]. However, there is scarce research on UFP removal using a DBD reactor packed with porous dielectric balls.…”
Section: Introductionmentioning
confidence: 99%